(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): How to carry out an evaluation of the component of promoting creativity and innovation based on the excellence model of the European Foundation for Quality Management (hereinafter EFQM) in the selected company? Purpose: The purpose of the research was to assess the level of development of the building blocks for promoting creativity and innovation, and based on the obtained results, formulate proposals for improvements. Method: In the theoretical part of the research, we focused on a descriptive approach, with the help of which we reviewed the professional literature and available empirical research. In the empirical part of the research, we basically performed a qualitative research method. In order to obtain primary data, we conducted a structured interview with five managers in all organizational units of the selected company. We performed basic and more demanding statistical processing on the information obtained in this way. Results: From the results of the empirical part of the research, it follows that the average value of the seven sub-building blocks is 3.27. The highest score of 4.5 was found for the fourth sub-building block Based on an understanding of the market and opportunities, they set precise goals for innovation that are supported by appropriate policies and resources. The lowest score of 2.2 was found for the seventh grade. Implementation of ideas in time frames that allow to maximize the benefits achieved. We have prepared suggestions for managers in the continuous improvement of the innovation process in the selected company. Organization: The research on the level of development of the building blocks for promoting creativity and innovation has a significant impact on the selected company, as we have prepared a starting point for the introduction of changes with the information obtained. Society: Investigating the degree of development of the building blocks of promoting creativity and innovation in the selected company can also contribute to the creation of an innovation culture in the economy and the wider social ecosystem. Originality: We have come to new knowledge about the level of development of the building blocks of promoting creativity and innovation, which increase the number of available information. We gained original insights into improving creativity and innovation. Limitations/further research: The research focused on one building block of the EFQM excellence model in one company. To gain a deeper understanding, it would be useful to conduct comparative analyzes between different companies.